Sustainability of cattle-crop plantations integrated production systems in Malaysia - Ismail, Dahlan (International Society for Development and Sustainability, 2014)
Evaluation on the sustainability of cattle-crop plantations integrated production system (CCPIS) was conducted in Federal Land Development Authority (FELDA) plantation schemes in Malaysia. The study was carried out in state of Pahang and Negeri Sembilan for cattle-oil palm integrated production systems (COPIS) and Kedah for cattle-rubber integrated production system (CRIPS). The outcome of the study shows that settlers or farmers in FELDA plantation schemes have increase their family income and standard of living through adoption of integrated farming system in the plantation. Number of farmers participates in CCPIS increased up to 150% within 24 years period. Amoeba diagram was used for evaluation of sustainable resources management and determination of negative driving factors in CCPIS based on triple bottom line (TBL) reporting. The technique integrates economic, environmental, and social components in the system. The study showed that all states gave strong negative drives on social factors. Economic and environmental factors contributed minimal problems in CCPIS. Social factors were the main management problems encountered by settlers in CCPIS. TBL indicators managed to identify the main problems of CCPIS and these indicators can be used in rectification program in order to ensure the sustainability of the integrated production systems.